Topology optimization of acoustic systems via the TOBS-GT method. - Castro, Thaís Almeida Ribeiro de (2022)
Topology optimization (TO) has been an active research area for over a century, and it is becoming more and more popular over the years in both academia and industry. One of the reasons of this growth is the rising computational power availability, that allows the usage of TO in increasingly complex real problems. The idea of the method is to find the entire structural layout (unknown a priori) with optimal performance regardless of the designers experience, thus offering a great design freedom in obtaining optimal structures. Although the TO procedures have reached a satisfactory level of maturity, one challenging scientific problem is how to set its framework to account for different physics. In this context, acoustics is identified as a topic open to research with few studies published up to date, when comparing to other physics. This project proposes and investigates the use of Topology Optimization of Binary Structures with Geometry Trimming (TOBS-GT) for solving acoustic problems. The TOBS-GT method combines binary design variables, sequential problem linearization, sensitivity filtering and an integer programming solver. The forward problem is solved via finite element analysis (FEA) and the sensitivities are computed with the adjoint method via automatic differentiation. The FEA mesh is separated from the optimization mesh, and the solid regions are removed from the analysis at each iteration to accurately model physical phenomena. The proposed methodology was applied to room acoustics and to an acoustic attenuator. Promising results were obtained, where the final topologies significantly reduced the sound pressure level in the objective domain. Studies show a relatively small computational time and that, as expected, the FEA is the bottleneck of the optimization process. For all cases proposed, the convergence criteria was met in quite few iterations, showing that the TOBS-GT approach can offer an advantage in this regard when comparing with classical TO methods.